PELATlHAN MUSIK PERKUSI PADASISWA-SISWI ANAK ASUH RUMAH ZAKAT DI SURAKARTA - Bondet Wrahatnala (Abdi Seni, 2016)
Music more offers convenience in a noise through the things that exist in the environment around us. As will be studied and implemented in the program this time is a percussion instrument. Some of the convenience offered by this type of instrument include (1) issued monofon tone, (2) much easier to play, because in general this instrument sounded by being beaten by hand or with the aid of a stick, (3) easy access to them, because often found in the environment, and (4) can be played in groups of numbers. Through this program, the training element of the development of ethnic percussion instruments that adopt the archipelago combined with Islamic music can be applied. Especially in the details of the program, one of the material is the music and vocals. The model adopted is the application of science and technology Interest and Talent Search Method for music, which is to determine some of the kids that can play music by the way they play percussion instruments are struck directly by hand ie jeembe and trebang, and percussion instruments are struck using a stick that is tom-tom and dog-dog. The second is the method of the Clinical Workshop, which demonstrates percussion. The mechanism adopted is to divide the participants into several groups, each group was accompanied by training team members. This activity aims to end to form an archipelago of ethnic percussion groups, with ethnic percussion pattern of the archipelago which consists of children who have a basic non-art. In this case, the foster children from Rumah Zakat in Surakarta. Further outcomes are able to provide container staging of this musical group to be able to participate.Key words: Pelatihan musik perkusi, Siswa-siswi anak asuh Rumah Zakat Surakarta